2013
DOI: 10.1007/s10591-013-9289-8
|View full text |Cite
|
Sign up to set email alerts
|

Attachment, Infidelity, and Loneliness in College Students Involved in a Romantic Relationship: The Role of Relationship Satisfaction, Morbidity, and Prayer for Partner

Abstract: This study examined the mediating effects of relationship satisfaction, prayer for a partner, and morbidity in the relationship between attachment and loneliness, infidelity and loneliness, and psychological morbidity and loneliness, in college students involved in a romantic relationship. Participants were students in an introductory course on family development. This study examined only students (n = 345) who were involved in a romantic relationship. The average age of participants was 19.46 (SD = 1.92) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 89 publications
(119 reference statements)
2
13
1
Order By: Relevance
“…HANGEN, CRASTA, AND ROGGE Alternatively, the results could suggest that it is individuals in thriving relationships who are most able to successfully navigate the dynamics of CNM relationships with active communication and sensitivity. These results stand in stark contrast to a growing body of cross-sectional research linking EDSA to lower relationship quality in monogamous relationships (e.g., Atkins, Baucom, & Jacobson, 2001;Mark et al, 2011;Pereira et al, 2014;Whisman et al, 2007). Similarly, longitudinal studies have shown that lower relationship satisfaction and lower commitment significantly predict future EDSA (Drigotas, Safstrom, & Gentilia, 1999;Maddox Shaw, Rhoades, Allen, Stanley, & Markman, 2013).…”
Section: Consensual Nonmonogamous (Cnm) Relationshipscontrasting
confidence: 90%
See 2 more Smart Citations
“…HANGEN, CRASTA, AND ROGGE Alternatively, the results could suggest that it is individuals in thriving relationships who are most able to successfully navigate the dynamics of CNM relationships with active communication and sensitivity. These results stand in stark contrast to a growing body of cross-sectional research linking EDSA to lower relationship quality in monogamous relationships (e.g., Atkins, Baucom, & Jacobson, 2001;Mark et al, 2011;Pereira et al, 2014;Whisman et al, 2007). Similarly, longitudinal studies have shown that lower relationship satisfaction and lower commitment significantly predict future EDSA (Drigotas, Safstrom, & Gentilia, 1999;Maddox Shaw, Rhoades, Allen, Stanley, & Markman, 2013).…”
Section: Consensual Nonmonogamous (Cnm) Relationshipscontrasting
confidence: 90%
“…Consistent with this, the individuals in this group reported some of the lowest relationship and individual functioning. These findings align with previous research on infidelity (Atkins et al, 2001;Mark et al, 2011;Pereira et al, 2014;Whisman et al, 2007) as well as previous studies which found that monogamous couples with one partner engaging in EDSA had lower relationship quality when compared to strictly monogamous and CNM relationships (LaSala, 2004;Rodrigues et al, 2016). Taken together, this suggests that EDSA occurring in the absence of mutual consent, comfort, and communication could have devastating effects on relationship quality and/or could represent a maladaptive reaction to a failing relationship.…”
Section: Consensual Nonmonogamous (Cnm) Relationshipssupporting
confidence: 90%
See 1 more Smart Citation
“…Although the effect of attachment on relationship satisfaction is well established, both for the general population (Butzer & Campbell, 2008;Pereira et al, 2014) and for CSA survivors (Meyer et al, 2017;Tocker et al, 2017;Wolfe et al, 2004), this study adds new insights by showing romantic partner attachment avoidance and anxiety only mediating the association of CSA with relationship satisfaction on a pathway that also includes sexual shame. This is consistent with Lassri et al's (2018) study in which romantic partner attachment did not mediate the association between CSA and relationship satisfaction.…”
Section: Discussionmentioning
confidence: 82%
“…According to Weiss (1973), who carried out a study on loneliness, the impact of social support resources on loneliness is clear. The existing literature indicated that loneliness associated with a lack of emotional contact with friends and family (Bondevik & Skogstad, 1998;Hawkley, Browne, & Cacioppo, 2005), trust in and access to parents (De Minzi, 2010), attachment (Akdoğan, 2017;Helm et al, 2020), social support and social commitment (Li-Jane & Shi-Kai, 2007;Duru, 2008b;Zhao, Kong, & Wang, 2013), the quality of the romantic relationship, and relationship satisfaction (Elmien, Rozanne, & Alberta, 2016;Özdemir & Tuncay, 2008;Pereira, Taysi, Orcan, & Fincham, 2014;Türk & Yıldız, 2017).…”
Section: Introductionmentioning
confidence: 99%